Optimization of combined hydrothermal and mechanical refining pretreatment of forest residue biomass for maximum sugar release during enzymatic hydrolysis - Hossain, Md Shahadat; Therasme, Obste; Volk, Timothy A.; Kumar, Vinod; Kumar, Deepak (MDPI, 2024)
This study aimed to investigate the effect of chemical-free two-stage hydrothermal and mechanical refining pretreatment on improving the sugar yields during enzymatic hydrolysis of forest residue biomass (FRB) and optimize the pretreatment conditions. Hot-water pretreatment experiments were performed using a central composite design for three variables: temperature (160–200 °C), time (10–20 min), and solid loading (10–20%). Hydrothermally pretreated biomass was subsequently pretreated using three cycles of disk refining. The combined pretreatment was found to be highly effective in enhancing sugar yields during enzymatic hydrolysis, with almost 99% cellulose conversion for biomass pretreated at 213.64 °C, 15 min, and 15% solid loading. However, the xylose concentrations in the hydrolysate were found to be low under these conditions due to sugar degradation. Thus, less severe optimum pretreatment conditions (194.78 °C, 12.90 min, and 13.42% solid loading) were predicted using a second-order polynomial model. The response surface model optimized the hydrothermal pretreatment of FRB and predicted the glucan, xylan, and overall conversions of 94.57%, 79.78%, and 87.84%, respectively, after the enzymatic hydrolysis. The model-predicted biomass conversion values were validated by the experimental results.
Keywords: hydrothermal pretreatment; disk milling; forest residue biomass; enzymatic hydrolysis; response surface methodology (RSM); central composite design (CCD); 40 Engineering; 33 Built Environment and Design; 51 Physical Sciences; 7 Affordable and Clean Energy